PENGARUH PENALARAN ETIS DAN FAKTOR-FAKTOR PRIBADI TERHADAP SENSITIVITAS ETIS PADA MAHASISWA AKUNTANSI - Ega Megarina Iswarini; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
This study aims to analyze whether the ethical reasoning and personal factors which is owned by students effect on ethical sensitivity it has. Personal factors of accounting students in this study consist of idelism, relativism, locus of control and demographic factors (genders, academic, and age). Data obtained by distributing questionnaires to the six semesters of accounting students which are studying in Semarang university include Diponegoro University, UNIKA Soegija Pranata and Dian Nuswantoro University. The number of questionnaires that were distributed directly using purposinve sampling are 200 pieces, which can be used for sample analysis are 141 pieces. The analysis tools that multiple regression in SPSS Ver.17. The results of this study found that ethical reasoning has significant influence on ethical sensitivity. Relativism also has a significant effect on ethical sensitivity. People that have more internal locus of control have a strong influence on sensitivity than external. Of the three demographic factors, only gender had a significant influence on ethical sensitivity.